P.Oxy. 1089 and the secret interview of Flaccus with the anti-Semites Isidoros and Dionysios. Text and translation (Circe de clásicos y modernos, 2018)
In this work we offer the translation from Greek to Spanish of P. Oxy. 1089, with introduction and notes. It is a papyrus that refers to a secret interview that took place in the Serapeum of Alexandria between the Roman prefect Flaccus, who ruled Egypt from 32 to 38 AD, and two politicians belonging to the national-anti-Semitic sector of the port-city, Isidoros and Dionysios. The importance of the papyrus, which is shown as a historical narrative, resides in its connection with real events; it has been considered as an antecedent of the first pogrom against the Jews of Alexandria occurred in the year 38.
Keywords: P.Oxy. 1089; interview; Alexandria; anti-Semites; Flaccus